PERANCANGAN SISTEM INFORMASI KELENGKAPAN PENGISIAN RINGKASAN PASIEN PULANG (RM 5) RAWAT INAP DI RS X KOTA BANDUNG - Winda Putri Indah Lestari; Sali Setiatin; Yuda Syahidin (Media Bina Ilmiah, 2022)
The research aimed for the inpatient discharge summary information system design completeness at Rumah Sakit X. The research was used qualitative methode with descriptive approach. Software development used waterfall method. From the result research the problems are: (1). There was a the inpatient medical resume as not complet. (2). Process of checking the completeness and preparing reports still done manually, that is data patient repeated written using Microsoft excel. The suggestion in this research are : (1). Having a socialization to all health officers about filling medical resume. (2). Design information system of the inpatient medical information system design completeness that more effective and efficient to operate.